A case series of invasive pneumococcal disease in children - B., Baburaj; Cherian, Carol Sara; Abraham, Jacob; Jacob, Aneeta Mary (International Journal of Contemporary Pediatrics, 2023)
Invasive pneumococcal disease (IPD) has a high clinical burden, particularly among children in developing countries. We presented 4 cases of IPD in children who were admitted to Pushpagiri institute of medical science and research centre, Kerala between 2021 and 2022. While our first 3 patients had milder course of disease, our fourth patient who presented with severe pneumonia with pleural effusion had poor outcome. The fact that three out of four of our patients have not received pneumococcal vaccination marks the necessity of this vaccine to prevent IPD in children.